Strategi Dakwah Digital dalam Podcast Escape Ustad Felix Siauw - Fahmi, Muhammad; Syarifudin, Achmad; Walian, Anang (INSTITUT PEMBINA ROHANI ISLAM JAKARTA, 2025)
In this digital era, da'wah strategies have also undergone a transformation, from conventional methods to more modern and creative methods. Therefore, the background of this research is that many young people are reluctant to listen to advice such as lectures because they are considered boring and time-consuming. The purpose of this study is to determine whether the use of Podcasts in delivering da'wah is able to make young people, in particular, return to listening to lectures. This research was conducted qualitatively using a descriptive research design. Based on the results of the study, it shows that Ustadz Felix Siauw utilizes the Escape podcast as a digital da'wah medium that is adaptive to technological developments and the characteristics of young audiences. Through a persuasive, dialogical, and contextual communication style, he successfully conveys Islamic messages in a light but meaningful manner. The da'wah strategy implemented emphasizes a balance between emotional and rational aspects, and is supported by strong narrative skills.